Instrumento para evaluar ideas de negocio en el sector lácteo del cantón Latacunga - Espinel Viteri, Jennifer Fransheska (2017)
The research aims to characterize the small entrepreneurs of the dairy sector in Latacunga through an instrument of evaluation of the business idea. According to the National Institute of Statistics and Censuses of 2016, the fastest growing productive sector in the province of Cotopaxi was dairy. For the development of the study the tool Lona is analyzed that allows to verify the form in which the organizations create, the deliver and the value capture economic; Subsequent to this it was adapted to the characteristics and conditions of the dairy sector. In order to declare the validity of the content of the instrument, a trial of three experts was submitted, the same ones that they contributed with suggestions and after obtaining the approval, the application was carried out. The research methodology is based on a quantitative approach, with non-probabilistic sampling for convenience and cross-sectional research; for this there is no need to run the sample since the researchers choose who to interview the instrument through the Canvas model. Subsequently, 11 new enterprises are evaluated in the second stage of business development in which businesses born from 1 to 3.5 years of maturity create value and competitiveness in the market….